Entraining stepping movements of Parkinson's patients to alternating subthalamic nucleus deep brain stimulation - Fischer, P; He, S; de Roquemaurel, A; Akram, H; Foltynie, T; Limousin, P; Zrinzo, L; Hyam, J; Cagnan, H; Brown, P; Tan, H (Society for Neuroscience, 2020)
Patients with advanced Parkinson's can be treated by deep brain stimulation of the subthalamic nucleus (STN). This affords a unique opportunity to record from this nucleus and stimulate it in a controlled manner. Previous work has shown that activity in the STN is modulated in a rhythmic pattern when Parkinson's patients perform stepping movements, raising the question whether the STN is involved in the dynamic control of stepping. To answer this question, we tested whether an alternating stimulation pattern resembling the stepping-related modulation of activity in the STN could entrain patients' stepping movements as evidence of the STN's involvement in stepping control. Group analyses of ten Parkinson's patients (one female) showed that alternating stimulation significantly entrained stepping rhythms. We found a remarkably consistent alignment between the stepping and stimulation cycle when the stimulation speed was close to the stepping speed in the five patients that demonstrated significant individual entrainment to the stimulation cycle. Our study suggests that the STN is causally involved in dynamic control of step timing, and motivates further exploration of this biomimetic stimulation pattern as a potential basis for the development of deep brain stimulation strategies to ameliorate gait impairments. SIGNIFICANCE STATEMENT We test if the subthalamic nucleus in humans is causally involved in controlling stepping movements. To this end we studied patients with Parkinson's disease who have undergone therapeutic deep brain stimulation, as in these individuals we can stimulate the subthalamic nuclei in a controlled manner. We developed an alternating pattern of stimulation that mimics the pattern of activity modulation recorded in this nucleus during stepping. The alternating DBS could entrain patients' stepping rhythm, suggesting a causal role of the STN in dynamic gait control. This type of stimulation may potentially form the basis for improved DBS strategies for gait.